2016
DOI: 10.2106/jbjs.15.01025
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine Supination Strength Following Distal Biceps Repair

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…However, in clinical practice, restoration of full supination strength comparable to that of the uninjured arm rarely occurs during a full range of motion 17, 4, 7. A study using postoperative magnetic resonance imaging scans verified an anatomic reattachment site and radial protuberance preservation, but the injured arm recovered 81.3% ± 16.4% of isometric supination strength normalized to the contralateral side in 60° of forearm supination ( P = .027) 17 …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, in clinical practice, restoration of full supination strength comparable to that of the uninjured arm rarely occurs during a full range of motion 17, 4, 7. A study using postoperative magnetic resonance imaging scans verified an anatomic reattachment site and radial protuberance preservation, but the injured arm recovered 81.3% ± 16.4% of isometric supination strength normalized to the contralateral side in 60° of forearm supination ( P = .027) 17 …”
mentioning
confidence: 98%
“…Cadaveric mechanical studies have demonstrated that reattaching the distal biceps tendon to its anatomic footprint and preserving the radial protuberance lead to a return of native supination moment arms and flexion strength 16, 19, 21. However, in clinical practice, restoration of full supination strength comparable to that of the uninjured arm rarely occurs during a full range of motion 17, 4, 7. A study using postoperative magnetic resonance imaging scans verified an anatomic reattachment site and radial protuberance preservation, but the injured arm recovered 81.3% ± 16.4% of isometric supination strength normalized to the contralateral side in 60° of forearm supination ( P = .027) 17 …”
mentioning
confidence: 99%
“…Acute anatomic surgical repair of distal biceps brachii tendon has been shown to improve functional outcomes, strength, and muscle endurance after distal biceps rupture. 1 , 16 , 22 , 23 Cortical button fixation has been shown to outperform bone tunnels, intraosseous screws, and suture anchors in biomechanical studies. 7 , 12 , 16 , 19 As noted previously, the most common major complication following surgery is PIN palsy, and unicortical button fixation may have the advantage of avoiding inadvertent injury to the PIN.…”
Section: Discussionmentioning
confidence: 99%
“…This more posterior attachment improves the rotational moment arm of the distal biceps to facilitate its most important function, supination. 2,[4][5][6] And because forceful retraction through the anterior wound is minimized, direct retraction of the nerves is reduced, leading to a lower reported rates of both LABC and PIN injury. 3 The greatest limitation of the 2-incision technique is that it carries a slightly higher rate of HO and synostis.…”
Section: Discussionmentioning
confidence: 99%
“…3 The 2-incision approach yields direct access to the tuberosity and allows restoration of the anatomic attachment site, which improves supination strength, the most important function of the distal biceps. 2,[4][5][6] And because forceful retraction through the anterior wound is reduced, direct retraction of the nerves is reduced, leading to a lower reported rate of nerve injury. 3 Although the rate of heterotopic ossification (HO) and synostis is slightly higher, the use of indomethacin prophylaxis has been shown to mitigate them.…”
mentioning
confidence: 99%